University-Industry Forum 2010 - UMP, PNC (Penerbit UMP, 2010)
This year's Universiti Malaysia Pahang's (UMP) University-Industry Forum, themed "Managing Performance for Productive University Industry Collaborations", was held on May 27 at the MS Garden Hotel in Kuantan, Pahang.